The Effect Of Pitch Ratio On Screw Turbine Performance With Tip Fin - Adiwidodo, Satworo; Ahmad, Masrur Maulana (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
A water turbine is an energy conversion machine that converts water head into shaft movement. In screw-type turbines, performance is influenced by several parameters including outer diameter, inner diameter, rotor length, head angle, number of blades, and pitch distance. This research uses a screw turbine type with a tip fin. The research aims to determine the performance of screw turbines with tip fins on mechanical power and efficiency. The research independent variables consist of pitch ratio and flow rate. The pitch ratio variations used are 1.2; 1.4 and 1.6 while the variations in flow rate used are 3 l/s, 3.5 l/s, and 4 l/s. The method used in this research is experimental. This study's data analysis employed the two-way Anova method with an alpha (α) of 5%. Anova's results show that the P-value of the interaction of the two independent variables, pitch ratio and water discharge, is <0.05, meaning that the independent variables have a significant influence on the performance of the screw turbine. The highest turbine performance results were at a pitch ratio of 1.4 at a water flow rate of 4 l/s resulting in an efficiency value of 34.91% and a mechanical power value of 6.82 watts at a rotational speed of 125 RPM. The lowest turbine performance results at a pitch ratio of 1.2 with a flow rate of 3 l/s resulting in an efficiency of 22.64% and a mechanical power of 3.32 watts at a rotational speed of 56 RPM.